Aspectos de solos salinizados e remediação no Estado de Sergipe - Oliveira, Paulo Alceu dos Santos (2015)
Soil salinization and sodification are amongst the main land degradation processes. This evergrowing issue reaches worldwide proportions and takes place mostly in arid and semiarid regions of the world, including the Brazilian northeast and the state of Sergipe. It is caused mostly by anthropic activities such as inadequately irrigated agriculture, soil preparation and indiscriminate use of chemical fertilizers, in combination with weather conditions and soil characteristics. These phenomena have led to the decrease in agricultural productivity, increased soil treatment coss and land abandonment. Solutions to this problem demand integrated approaches that combine knowledge in agricultural, environmental, social and economic sciences. The goal of this work is to investigate predisposing conditions and the presence of soil salinization processes, identifying its inception and manifestation elements on the land reform settlement project Jacaré-Curituba, as well as to test the development of the plant Chrysopogon zizanioides (L.) Roberty in the settlement soil, analyzing salty soil´s potential for phytoremediation. The study was guided by theoretical frameworks that address the causes, consequences, control and mitigation options for the processes of soil salinization; field research for conduction of interviews; collection and analysis of different soils; and experiments with ten genotypes of the Chrysopogon zizanioides (L.) Robertyspecies in greenhouse soils with three different salinization levels. The study concludes by identifying, on the settlement project, the existence of salty soil due to pedoclimatic conditions and the adoption of agricultural techniques that foster the salinization process. On the greenhouse experiment there were significant differences of plant development when exposed to increased soil salinity and sodicity. The level of soil salts extraction was low, however, due to the salinity and sodicity tolerance showed by the plant, it was identified promising potential of vetiver for phytoremediation of saline soils by mechanisms related to improving the conditions of soil by growing roots and leaves.